Is there any association between vitamin D deficiency and anti-thyroid peroxidase positive hypothyroidism: A cross-sectional study - Dr. Meenakshi Shankar; Dr. Mukul Singh (International Journal of Medical Research and Review, 2020)
Background: Vitamin D deficiency is prevalent worldwide and it is believed to have a role as an immune modulator. However, the association between vitamin D levels and anti-thyroid peroxidase positive (TPOAb) hypothyroidism is still controversial.Aim: To elucidate the association between vitamin D levels and anti-thyroid peroxidase (TPOAb) positive hypothyroidism.Materials and Methods: Serum Vitamin D, thyroid peroxidase antibody, and thyroid function test were measured in 105 patients, who were sub-grouped into the TPOAb positive and TPOAb negative hypothyroidism category.Results: Vitamin D level, was found significantly lower in patients with TPOAb positive hypothyroidism as compared to patients TPOAb negative hypothyroidism (13.275.18vs. 17.746.03ng/ml, respectively, P<0.05), as well as between patients with TPOAb positive hypothyroidism and control group (13.275.18vs. 29.669.41 ng/ml, respectively, P<0.05). Within the patients' group, there was a significant negative correlation between serum 25 (OH) vitamin D and TSH (r=−0.438, P<0.05), anti-TPO (r=−0.275, P<0.05). Furthermore, insignificant positive correlations were recorded between serum 25 (OH) vitamin D, and each of T3, T4 (r=–0.056, 0.097, P>0.05).Conclusion: The current study observed significant low levels of 25(OH)D3 in TPOAb positive hypothyroid patients.